2024
DOI: 10.1158/2159-8290.cd-23-0426
|View full text |Cite
|
Sign up to set email alerts
|

Senescent CAFs Mediate Immunosuppression and Drive Breast Cancer Progression

Jiayu Ye,
John M. Baer,
Douglas V. Faget
et al.

Abstract: The tumor microenvironment (TME) profoundly influences tumorigenesis, with gene expression in the breast TME capable of predicting clinical outcomes. The TME is complex and includes distinct cancer-associated fibroblast (CAF) subtypes whose contribution to tumorigenesis remains unclear. Here, we identify a subset of myofibroblast CAFs (myCAF) that are senescent (senCAF) in mouse and human breast tumors. Utilizing the MMTV-PyMT;INK-ATTAC (INK) mouse model, we found that senCAF-secreted extracellular matrix spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…Several studies using syngeneic tumor models in immune-competent mice showed that the SASP can prevent tumor rejection by inducing an immunosuppressive TME 710 . For example, prolonged exposure to SASP factors such as type 1 interferon and IL-6 were shown to downregulate immune cell functions 1113 and to interfere with the tumor immune response mediated by T and NK cells 79 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using syngeneic tumor models in immune-competent mice showed that the SASP can prevent tumor rejection by inducing an immunosuppressive TME 710 . For example, prolonged exposure to SASP factors such as type 1 interferon and IL-6 were shown to downregulate immune cell functions 1113 and to interfere with the tumor immune response mediated by T and NK cells 79 .…”
Section: Introductionmentioning
confidence: 99%